2001
DOI: 10.1139/z01-132
|View full text |Cite
|
Sign up to set email alerts
|

Production de composés indoliques rhizogènes par le ver de terre Lumbricus terrestris

Abstract: In vitro application of total gross extract of earthworms (Lumbricus terrestris) in diverse dilutions stimulates rhizogenesis in young bean plants (Phaseolus vulgaris). The observed effect is similar to that of indol acetic acid, a well-known growth enhancer in plants, used here as a control in various concentrations. Fragmentation of worm extract by column chromatography results in three groups of fractions. Only the polar group of fractions has a significant rhizogenous effect, which is, however, inferior to… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0
4

Year Published

2004
2004
2023
2023

Publication Types

Select...
6
2
1

Relationship

1
8

Authors

Journals

citations
Cited by 14 publications
(9 citation statements)
references
References 29 publications
0
5
0
4
Order By: Relevance
“…Mycorrhizal colonization (Cavender et al, 2003), microbial activity (Domínguez, 2004) and suppressiveness of soilborne plant pathogens (Hoitink and Boehm, 1999;Szczech, 1999;Szcech and Smolinska, 2001;Scheuerell et al, 2005;Noble and Coventry, 2005;Termorshuizen et al, 2006) have shown to be enhanced through the addition of compost and vermicompost to a potting media or as a soil amendment. Furthermore, biologically active metabolites such as plant growth regulators (Tomati and Galli, 1995;El Harti et al, 2001) and humates (Atiyeh et al, 2002;Canellas et al, 2002) have been discovered in vermicomposted materials.…”
Section: Discussionmentioning
confidence: 99%
“…Mycorrhizal colonization (Cavender et al, 2003), microbial activity (Domínguez, 2004) and suppressiveness of soilborne plant pathogens (Hoitink and Boehm, 1999;Szczech, 1999;Szcech and Smolinska, 2001;Scheuerell et al, 2005;Noble and Coventry, 2005;Termorshuizen et al, 2006) have shown to be enhanced through the addition of compost and vermicompost to a potting media or as a soil amendment. Furthermore, biologically active metabolites such as plant growth regulators (Tomati and Galli, 1995;El Harti et al, 2001) and humates (Atiyeh et al, 2002;Canellas et al, 2002) have been discovered in vermicomposted materials.…”
Section: Discussionmentioning
confidence: 99%
“…The positive effect of earthworm mucus was ascribed to rhizogenic substances similar to indole acetic acid (El Harti et al, 2001). The predominating negative effect might however have been due to high concentrations of ammonium in earthworm mucus that might induce seed dormancy and/or delay germination (Satchell, 1967).…”
Section: Secretion Of Mucusmentioning
confidence: 99%
“…The clone T-78 performed best in respect of branches per plant (7.33) as compared to other clones (Choubey et al 2013). Better production of vegetative parts in the present investigation might be due to the presence of various biologically active metabolites such as plant growth regulators (Tomati and Galli 1995;El Harti et al 2001) and humates (Atiyeh et al 2002;Canellas et al 2002;Forde and Lorenzo 2001).…”
Section: Resultsmentioning
confidence: 74%